Factors Associated with Mortality Among Patients with Drug-Resistant Pulmonary Tuberculosis in Sumatera, Indonesia, 2020–2024 - Wahyuni, Fajriani Dwi; Widoyo, Ratno; Syafrawati, Syafrawati (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Drug-resistant tuberculosis (DR-TB) remains a major public health problem due to its high mortality and low treatment success rates. Sumatra is one of the regions in Indonesia with a high burden of DR-TB mortality. This study aimed to analyze factors associated with mortality among patients with drug-resistant pulmonary tuberculosis in Sumatra during 2020–2024. This study used a quantitative analytical observational design with a retrospective cohort approach utilizing secondary data from the Tuberculosis Information System (SITB) of the Ministry of Health of Indonesia. A total sampling technique was applied to all eligible DR-TB patients. The dependent variable was mortality during treatment, while independent variables included age, sex, employment status, HIV status, type of health facility, residential area, and treatment history. Data were analyzed using univariate, bivariable, and multivariable analyses. Multivariable analysis was performed to identify factors associated with mortality after adjustment for confounding factors. The results showed that age and treatment history were significantly associated with mortality (p<0.05). Patients aged ≥45 years had a 1.60 times higher risk of death compared to younger patients, while previously treated patients had a 1.32 times higher risk of mortality compared to new cases. Other variables were not significantly associated with mortality. These findings highlight the importance of closer monitoring among older and previously treated DR-TB patients.